Participation of Muslims in Education Policy Perspective and Provisions - Kaushal, Savita (JOURNAL OF INDIAN EDUCATION, 2014)
This paper presents analytical review of the policy perspective and schemes initiated to facilitate inclusion and participation of Muslims in education in India. It seeks to map the measures and resultant outcomes, in an effort to identify gaps and suggest suitable initiatives to better understand the drivers and facilitators of the exclusion, and how the challenge for inclusion of Muslims in education in India could not be met. In the light of the available data, the paper re-examines the existing government policies to tackle the educational backwardness of Muslims in terms of the extent to which they have been successful in dealing with their problems.